Analisis Kepatuhan Karyawan PT Cipta Megaswara Televisi (Kompas TV) Divisi Traffic - Utami, Natasia Tri; Marsofiyati, Marsofiyati; Maulida, Ervina (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Employee compliance is a form of obedience from a person's attitude in complying with certain regulations or provisions related to work. This study aims to determine and analyze employee compliance at PT Cipta Megaswara Televisi (Kompas TV) Traffic Division. This study uses a qualitative research method, a type of research where researchers rely on the views of participants or informants. Researchers took four samples related to the research topic. These four samples provided researchers with various information or important aspects that improve or enrich understanding of the perspective being studied. Data collection techniques included observation, interviews, and documentation. The results of this study indicate that employee compliance in the traffic division has improved significantly due to the regulations enforced by the company and employees' ability to demonstrate a responsible attitude and professionalism when implementing compliance in the workplace. Factors influencing employee compliance can be improved through motivation, leadership, and effective communication, thus employee compliance can be significantly improved and to encourage greater compliance. Strategies to improve employee compliance require companies to develop more in-depth strategies such as weekly training and more effective supervision. Therefore, researchers hope that the results of this study can provide suggestions and insights regarding employee compliance in any company.